7. PENGARUH PELATIHAN DAN PROMOSI TERHADAP PRESTASI KERJA STUDI PADA PEGAWAI DI KANTOR KECAMATAN BLIMBING KOTA MALANG - Malang, Sekolah Tinggi Ilmu Administrasi (STIA) (Ilmu Administrasi, 2019)
AbstractTraining and development is defined as the preparation of individuals to assumedifferent or higher responsibilities within the organization. Training anddevelopment are typically associated with the necessary emotional and skillupgrading to perform better jobs. Development stands on the fact that anemployee will need the knowledge, skills and abilities that develop so thatemployees can work well in a series of succession positions that will be livedduring his career. Providing training to employees can also mean improvingemployee standards, which indicate an increase in the ability and skills ofemployees to perform certain jobs or tasks. One of the reasons why companiesprovide training to employees is to improve employee performance. With theimprovement of employee performance is expected to goals and objectives set bythe company can continue to run smoothly and in accordance with the set by themanagement company. A form of motivation that can effectively encourage aperson to participate actively in an organization, among others, is theopportunity to feel progress in his work, both in position and authority. Theopportunity to move forward is often called promotion. Promotion means trustand acknowledgment of the employee's ability and skills to occupy a higherposition.Keywords: Training, Promotion, Job Performance